Fistulating diverticulitis: a distinct clinical entity? - Papagrigoriadis, Savvas; Brandimarte, Giovanni; Tursi, Antonio (Frontiers in Medicine, 2025)
IntroductionDiverticular disease (DD) of the colon has a number of phenotypes, including asymptomatic diverticulosis and complicated diverticulitis with bowel perforation or bleeding. The factor that affects the phenotype of this condition and leads to a wide range of clinical presentations is unknown. The formation of fistulas associated with diverticulitis has long been recognized, and they are treated according to ad hoc indications. We hypothesized that the formation of fistulas in diverticular disease exhibits such a wide range of variable anatomic features that it may be considered a distinct form of the condition, fistulating diverticulitis (FD).MethodsWe conducted a narrative review based on 50 years of publications covering a wide range of diverticulitis-associated fistulas, both common and uncommon.ResultsWhile there is abundant literature on common fistulas, such as colovesical and colovaginal fistulas, little is known about rarer fistulas, such as coloenteric fistulas, colocutaneous fistulas, and genitourinary tract fistulas. The majority of these fistulas are treated surgically, which is in contrast to the trend toward conservative management that is predominant in acute or chronic diverticulitis.DiscussionEpidemiological and histological evidence support the hypothesis that FD may be a feature of chronic DD that requires individual management. Histopathology shows similarities with Crohn’s disease. It remains unknown which underlying immune or genetic factors may be affecting the clinical presentation of these patients, leading to fistulation. We contend that there is adequate published evidence to characterize a distinct phenotype of FD that can involve the entire GI tract and other organs. Surgical guidelines may need to be modified to treat this small but important group, which predominantly requires surgical treatment.